Sports medicine: a century of progress - Tipton, C. M. (The Journal of Nutrition, 1997)
According to the International Olympic Committee, it is the responsibility of the sports medicine profession to care for the health and welfare of Olympic athletes, treat and prevent injuries, conduct medical examinations, evaluate performance capacity, provide nutritional advice, prescribe and supervise training programs, and to monitor substance use. Implicit in these functions is to assist Olympic athletes in achieving the objectives of the Olympic Motto (Citius, Altius, Fortius), which is to become faster, higher, and stronger. During the past Olympiads, athletic performance has increased, as indicated by times for the men's marathon (-28%) or by the distance covered in the women's javelin throw (+80%). However, the fulfillment of these responsibilities was a slow and protracted process, as demonstrated by the facts that medical examinations were not required until 1920, that 28 years elapsed before an official team physician was appointed, and that women had to wait until 1984 before sanction was given to compete in the marathon race. Doping was not defined until 1964, and monitoring of substance abuse did not materialize until after 1972. Although individuals have prepared for athletic competition since the ancient Olympics, the scientific foundations for various training prescriptions were not firmly established until the 1960s and 1970s. It was speculated that performance records will continue to improve in the next century because more scientific sports medicine information would be available and because such information would be better disseminated to athletes.